PURITY TESTING OF ARRIAH FMD VACCINES - D. A. Lozovoy; D. V. Mikhalishin; V. A. Starikov; M. I. Doronin; A. S. Sharypov (Ветеринария сегодня)
The paper demonstrates results of FMD vaccine testing for their inability to induce antibodies to FMD virus non-structural proteins (FMDV NSP antibodies) in cattle at different dates post vaccination. Subtype A, O, Asia-1 and SAT-2 cultural FMD virus replicated in baby hamster kidney suspension culture (ВНК-21/2-17) was used for vaccine production. FMDV antigen was inactivated with aminoethyl ethylenimine solution, and the suspension was subsequently purified. Non NSP-purified preparation was made to simulate presence of NSPs in the vaccine. ELISA test-kits were used for testing cattle sera collected before and after immunization for presence of 3ABC polyprotein-specific antibodies. Inoculation of cattle with non-purified preparation induced antibodies specific to FMDV NSPs in 87.5% animals on day 30, in 75% animals on day 44 and in 62.5% animals on day 132 post third immunization. All tested vaccines manufactured by the FGBI “ARRIAH” were demonstrated to induce no FMDV NSP antibodies suggesting their complete removal from the virus-containing suspension.